2005
DOI: 10.1099/mic.0.27955-0
|View full text |Cite
|
Sign up to set email alerts
|

Garlic blocks quorum sensing and promotes rapid clearing of pulmonary Pseudomonas aeruginosa infections

Abstract: The opportunistic human pathogen Pseudomonas aeruginosa is the predominant micro-organism of chronic lung infections in cystic fibrosis patients. P. aeruginosa colonizes the lungs by forming biofilm microcolonies throughout the lung. Quorum sensing (QS) renders the biofilm bacteria highly tolerant to otherwise lethal doses of antibiotics, and protects against the bactericidal activity of polymorphonuclear leukocytes (PMNs). It has been previously demonstrated that QS is inhibited by garlic extract. In this stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
216
1
6

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 372 publications
(230 citation statements)
references
References 20 publications
7
216
1
6
Order By: Relevance
“…This is in line with the findings reported by Sumiyoshi and Bjarnsholt et al [26,27] that A. sativum is a stimulator of the immune functions in rats.…”
Section: Discussionsupporting
confidence: 82%
“…This is in line with the findings reported by Sumiyoshi and Bjarnsholt et al [26,27] that A. sativum is a stimulator of the immune functions in rats.…”
Section: Discussionsupporting
confidence: 82%
“…Fresh garlic extract having strong anti-QS activity, injected subcutaneously for 7 d [1.5% of the mass of the mouse (20 g)] promoted rapid clearing of pulmonary P. aeruginosa infections [8] . Oral treatment with a fresh garlic extract for 14 d significantly lowered renal tissue destruction by anti-QS activity against P. aeruginosa infections in the mouse urinary tract infection model [22] .…”
Section: Discussionmentioning
confidence: 99%
“…However, the mode of action of many phytocompounds against the target organism is not clearly understood. Recent research has revealed that a few natural products including plant extracts have properties for modulating bacterial QS system, thereby reducing the virulence [8,9] . Syzygium cumini (S. cumini) and Pimenta dioica (P. dioica) are widely used medicinal plants having ability to alleviate bacterial infections and are used in traditional healing in different parts of the world.…”
Section: Introductionmentioning
confidence: 99%
“…Extracts of fruits (e.g., blackberries, cranberries, vanilla, and citrus) and herbs (e.g., rosemary and turmeric) and extracts and oils of other plant materials (garlic, clove, and cinnamon) and medicinal plants (e.g., betel nut and notoginsing) have all displayed QSI activity to some degree, typically found via inhibition of violacein production in the C. violaceum bioassay (137,138,(264)(265)(266)(267)(268)(269)(270)(271)(272)(273)(274)(275). In very few cases, however, have individual compounds been isolated or identified from these kinds of complex sources.…”
Section: Natural-product Qs Inhibitorsmentioning
confidence: 99%